INFLUENCE OF ECOLOGICAL AND GEOGRAPHICAL FACTORS ON THE FORMATION OF TRADITIONAL WATER USE CULTURE IN THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2025)
Based on the analysis of historical and geographical literature, the article reveals the ecological and geographical basis of the culture of traditional water use, which was formed over many centuries among the population of the Fergana Valley. Also, the measures used in the traditional water use culture to solve the environmental and geographical problems arising in the current water use system in the Fergana Valley are shown.